(3GdbGfhf GdhGLH GdJWHjb Ydi GdMSGH GdLGQj h GdGYJeGO GdeSJfOj (B:s (3OQGSI ebGQfI (B/s - (3GdLhGQj, SdWGf YHO Gddg eMehOs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2010)
(3bGYOI NVhY GdYbO dbGfhf GdEOGQj, GdbGfhf GdhGLH GdJWjSb Ydi GdMSGH GdLGQj, GdbGfhf GdhGLH GdJWHjb Ydi GdEYJeGO GdeSJfOjs
(3HHdjhZQGajG(B: (3U(B.177-188s
Keywords: (3GdEYJeGOGJ GdeSJfOjIs; (3GdHfhcs; (3GdYbhOs